Desempeño financiero y económico de alternativas de rehabilitación y renovación (R&R) de los cafetales agroforestales de la República Dominicana - Peguero, F.; Sánchez, R.O.; Peñaló, J.P.; Mejía, E.; Álvarez Varela, D.; Somarriba, E. (Centro Agronómico Tropical de Investigación y Enseñanza, 2021)
This report present different rehabilitation proposals of traditional agroforestry systems by introducing different coffee pruning systems and a proposal for renovation based on a new agroforestry coffee plantation based on coffee-banana-avocado with a yautía association during the first year. The rehabilitation schemes include seven different scenarios, including: coffee plantations without pruning; pruning of recepa according to the traditional pruning from the Dominican Republic distributed in one year (here called complete recepa in which the entire plantation is pruned in one year); two, three, four and five years; and a new system pruning that emulates the one used in Honduras. In all cases of rehabilitation and renovation, here are presented productive and financial projections throughout a cycle of 25-year-old crop and its impacts are analyzed.